Evaluation of ExpressTM 5-PHM and Titanium® 5-PHM Bac®-1 on high-risk receiving steers - M.P. Epp; Larry C. Hollis; B.B. Barnhardt; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2004)
One backgrounding field study was conducted at two locations to compare the health and performance of high-risk receiving steers given an ExpressTM 5-Pasteurella Haemolytica- Multocida (PHM) vaccine or a Titanium® 5-PHM Bac®-1 vaccine. At one location, calves given the Titanium 5-PHM vaccination had fewer first and second repulls (P<0.05). At the other location, calves given the Express 5-PHM vaccination had fewer initial pulls for respiratory disease and more hospital pen days at initial pull (P<0.05) than those given Titanium 5-PHM. No differences were measured at either location for mortality and average daily gain.
Keywords: Cattlemen' s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; ExpressTM 5-PHM; Titanium® 5-PHM Bac®-1; High risk steers